Anthropometric Analysis of Infraorbital Foramen in Adult Indian Dry Skull - Panicker, Johncy Itty; Kumar, Vishal; Veerannasetty, Vinay Kumar (Journal of Health and Allied Sciences NU, 2016)
Introduction: Normally infra orbital foramen (IOF) is situated on the anterior surface of maxilla about 1cm below the infra orbital margin (IOM) bilaterally. Infra orbital vessels and nerves emerge out through this foramen. Infra orbital nerve (ION) terminates by supplying skin over the lower eyelid, conjunctiva, lateral aspect of external surface of nose, upper lip, ala of the nose and the premolar teeth. Infra orbital vessels supply the area surrounding the IOF.Objective: To measure distance between superior part of the rim of the IOF to IOM (DIM) and the distance between the medial part of the rim of the IOF to lateral margin of the pyriform aperture (DIP). Compare the measurements of both sides. Compare our studies with other authors.Materials and methods: Sixty adult dry skulls of unknown sex were studied. Those skulls with damaged foramen were excluded. Measurements were done in millimetres. Result: The mean DIM on right side is 5.96 mm and on left side it is 6.07. Mean DIP on right side is 16.70 mm and on left side it is 16.63mm. We have observed that there is no much significant variations in respect to sides. Our values were within the range of many others value.Conclusion: Knowing exact location of IOF using different land mark is important for providing local anaesthesia in maxillofacial, plastic surgical operations and radio ablative neurotomy procedures. Thus information obtained is very useful IOF to avoid iatrogenic injury in the infra orbital area.
Keywords: Infraorbital margin; Infraorbital nerve; Piriform aperture; Indian population; maxillofacial surgery